EVALUASI PROGRAM KONSELING INDIVIDU DI SMP LABORATORIUM UNIVERSITAS NEGERI MALANG DENGAN MODEL DISCREPANCY - Eka Saputra, Wahyu Nanda (JURNAL FOKUS KONSELING, 2016)
This study aims to determine the discrepancy between the performance of individual counseling program on SMP Laboratorium Universitas Negeri Malang with standards. This study uses a standard of Guidelines for Performance Based Professional School Counselor Evaluation. Standard reads, âthe professional school counselor counsels individual students and small groups of students with identified needs/concernsâ. This study is an evaluation research using a discrepancy model. The approach used is a systems approach that is focused on the planning, implementation, and evaluation of individual counseling programs. Based on the data analysis of evaluation of individual counseling program in SMP Laboratorium Universitas Negeri Malang is still far from standard.Keyword: program evaluation, individual counseling, discrepancy model